Analyses of bacteriophages to Yersinia ruckeri and the salmon (Salmo salar L.) antibody response to the bacteriophages. - Strand, Amund (The University of Bergen, 2017)
New technologies for producing Atlantic salmon like the recirculation aquaculture systems (RAS) have gained popularity, and has overthrown the traditional flow through systems used in the freshwater stages of the Atlantic salmon production. This is a closed system with less water consumption, but extended water treatment. Despite the many advantages, opportunistic bacteria seem to thrive in in such closed and biological system. Since 2007 there have been an increase in the number of yersiniosis outbreaks. Many of these outbreaks have been in RAS, or in fish in sea cages that originated from infected RAS. The causative bacterium Yersinia ruckeri is capable of forming biofilm, thus making it hard to remove during disinfection. The bacterium can be treated with antibiotics, but facing the worldwide problem of antibiotic resistance, other alternatives are highly needed. One of the alternatives suggested is phage therapy. The long-forgotten method of using bacteria infecting viruses for biocontrol is now being studied again in aquaculture. Bacteriophages infecting Y. ruckeri were investigated in this study. Four different lytic phages and a cocktail including the four were delivered by ACD Pharmaceuticals. They were all tested in growing cultures of Y. ruckeri, where they all showed a good bacteriostatic effect. This indicates that the bacteriophages have a god potential for application in bio treatment of water and filters used in rearing of fish larva and fish. We studied the ability of salmon to produce anti-phage specific antibodies. This was done by immunization of salmon with phage as antigen, and the fish was injected three times with inactivated bacteriophages. The fish antisera were tested with enzyme-linked immunosorbent assay (ELISA), and all sera showed a high production of anti-phage antibodies in the fish given injection with phages alone or combined with adjuvance. The non-vaccinated (no phage antigen) control fish groups did not show any anti-phage antibody production. A neutralization test was ...